150 Implantable cardioverter-defibrillator lead complications and clinical effectiveness in patients with inherited cardiac conditions. (9th June 2011) - Bastiaenen, R; Ben-Nathan, S; Jones, S; Ward, D; Gallagher, M; Sharma, S; Behr, E R
Abstract : Background: Implantable cardioverter-defibrillator (ICD) therapy can reduce sudden death due to ventricular arrhythmia (VT/VF) but is not without complication, particularly in young patients who live for many years with a device in situ. We aimed to determine the ICD complication rate in our inherited cardiac condition (ICC) population compared with international reports. Particular importance was given to inappropriate shock therapy due to lead failure as there are new ICD technologies available. Methods: Patients with ICCs who had ICD implantation or box change between January 2006 and September 2009 were included. Data on clinical characteristics, complications and ICD therapies were obtained from pacing and hospital records. We compared our data with several ICD studies of patients with specific ICCs (Abstract 150 table 1 ). Results: 101 patients (mean age 44.1±14.8 years; 59 male) were included (idiopathic VF 15%; DCM 17%; ARVC 22%; HCM 21%; long QT syndrome 17%; Brugada syndrome 6%; others 2%). During a mean follow-up of 74.0±53.2 months 2 patients died (1 inappropriate shocks; 1 stroke). Indications were secondary prevention in 71.3% of patients. ICD types were 56.4% single chamber; 39.6% dual chamber; 4.0% biventricular. Appropriate therapy successfully terminated VT/VF in 27 (26.7%) patients 34.7% of secondary and 6.9% of primary prevention patients received appropriate therapy. Inappropriate therapy occurred in 18 (17.8%) patients and lead failure (noise/wear/fracture) in 22 (20.8%) patients (Abstract 150 table 2 ). 12 out of 18 inappropriate shocks were due to lead failure, 5 sensing errors (1 T-wave oversensing; 4 AF), 1 generator fault. 10/22 leads that failed were Medtronic Sprint Fidelis and these were responsible for 8/12 patients receiving inappropriate shocks including one death due to lead fracture. Comparison with other studies indicates a high lead failure rate due to the long follow-up period, similar to the LQT Study which reports 25% lead failure over 87 months (Abstract 150 table 1 ). With lead failure excluded the complication rate is comparable to shorter follow-up studies. Inappropriate and appropriate therapy rates are similar among all studies. Conclusions: There is a significant rate of ICD lead failure in patients with ICCs, which may be expected given the high frequency of Sprint Fidelis leads implanted during this period and the long follow-up. Our results compare favourably to other similar studies. The high rate of appropriate therapy highlights the clinical effectiveness of ICD intervention in secondary prevention. Lead complications may be lower with the use of new ICD technology in selected patients.